SEMANTIC FEATURES OF FORMAL SPEECH ACTS IN ENGLISH AND UZBEK: A COMPARATIVE ANALYSIS - Xoshimova Dilnoza Sobit qizi; Z. Raxmatullayev (Modern American Journals, 2025)
This article presents a comparative analysis of the semantic characteristics of formal speech acts in English and Uzbek. It explores the linguistic means specific to the formal style, their communicative functions, and the influence of social and cultural factors on the formation of speech acts. Furthermore, the study identifies similarities and differences in formal speech conventions in both English and Uzbek languages.
Keywords: Formal style, speech acts, semantics, pragmatics, comparative linguistics, conventional expressions